THE ANTI-BULLYING HANDBOOK (Author: Keith Sullivan) - Cleary, Mark (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2002)
KEITH SULLIVAN. The Anti-Bullying Handbook. Melbourne, Auckland, Oxford and New York: Oxford University Press (2000). 267 pp. NZ$29.95 (ISBN 0-19-558388-4)